2015
DOI: 10.1590/0100-2945-188/14
|View full text |Cite
|
Sign up to set email alerts
|

Parasitoides (Hymenoptera) De Moscas-Das-Frutas (Diptera: Tephritidae) No Semiárido Do Estado Do Ceará, Brasil

Abstract: RESUMO -As moscas-das-frutas (Diptera: Tephritidae), Anastrepha spp. e Ceratitis capitata (Wiedemann), são importantes pragas da fruticultura no Brasil. Para desenvolver um sistema sustentável de manejo integrado para este grupo de pragas, é fundamental conhecer os parasitoides (Hymenoptera) que podem regular as populações destes tefritídeos. Portanto, o objetivo deste estudo foi relatar a diversidade, a distribuição geográfica e as relações tritróficas dos himenópteros parasitoides de moscas-das-frutas, na re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Ferreira et al (2003) found the D. areolatus species associated with "Imperial" and "Tommy Atkins" mango fruits, with the highest frequency (94.1%) occurring in fruits of the "Imperial" variety. Of the 71 specimens of parasitoids found in the fruit growing region of Anagé, Bahia, 63 (88.7%) were of the D. areolatus species, being the most abundant (SÁ et al, 2012b), a fact also reported in other studies (ALVARENGA et al, 2009;MARSARO JÚNIOR et al, 2011a;ARAÚJO et al, 2015).…”
Section: Resultssupporting
confidence: 71%
“…Ferreira et al (2003) found the D. areolatus species associated with "Imperial" and "Tommy Atkins" mango fruits, with the highest frequency (94.1%) occurring in fruits of the "Imperial" variety. Of the 71 specimens of parasitoids found in the fruit growing region of Anagé, Bahia, 63 (88.7%) were of the D. areolatus species, being the most abundant (SÁ et al, 2012b), a fact also reported in other studies (ALVARENGA et al, 2009;MARSARO JÚNIOR et al, 2011a;ARAÚJO et al, 2015).…”
Section: Resultssupporting
confidence: 71%
“…Considering that the main form to control tephritidae in the orchards is through the application of insecticides (Härter et al, 2010), this low natural parasitism may be related to the frequent use of agrochemicals adopted as a management practice by the farmers. Araújo et al (2015) also found a small number of parasitoids, possibly due to the drought that occurred during the study period and also insecticides that were applied in conventional orchards. In addition to the use of agrochemicals, other factors may have contributed to the low natural parasitism found in this study, such as the host fruit and climate.…”
Section: Resultsmentioning
confidence: 89%
“…In addition to the use of agrochemicals, other factors may have contributed to the low natural parasitism found in this study, such as the host fruit and climate. Araújo et al (2015) emphasized that the species composition of parasitoids in a region can vary considerably, depending on a series of factors such as: climate, fruit flies diversity and infested fruits, among other aspects.…”
Section: Resultsmentioning
confidence: 99%
“…April, possibly due to a greater abundance and diversity of fruit flies then ( Table 1). The species Doryctobracon areolatus, Opius bellus, and Utetes anastrephae are also common in other Brazilian regions, parasitizing guava fruit fly larvae (Araujo et al, 2015). These species were already recorded in the region of Cariri in guavas (Azevedo et al, 2013).…”
Section: /8mentioning
confidence: 97%
“…Information on the population dynamics of fruit flies and their relation to biotic and abiotic factors must be gathered and properly interpreted, enabling the effectiveness of each region's control programs for regional control (Aluja et al, 2012). For instance, in the semiarid region of Ceará, braconids of the genera Doryctobracon (Szépligeti, 1911), Utetes (Viereck, 1913), and Opius (Lima, 1938) are common natural fruit fly parasitoids (Jahnke et al, 2014;Araujo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%